Hubungan Diabetes Melitus Tipe 2 dengan Derajat Obstruksi Penyakit Paru Obstruktif Kronik (PPOK) di RS. Royal Prima Periode 2022-2023 - Faskanita Maristella Nadapdap; Yehezkiel Benjamin Gultom; Sadarita Sitepu (Dinasti Research, 2024)
Type 2 Diabetes Mellitus (T2DM) is one of the most common comorbidities in patients with Chronic Obstructive Pulmonary Disease (COPD). COPD itself can be a risk factor in the development of T2DM through systemic inflammatory mechanisms caused by continuous and progressive exposure to cigarette smoke over time. To investigate the relationship between diabetes mellitus and the severity of COPD obstruction based on demographic data, spirometry test results, and fasting blood glucose (FBG) test results. This study used a quantitative method with an observational descriptive design. Sampling was done using total sampling technique with a cross-sectional survey design and a retrospective approach using secondary data. Out of 31 study subjects diagnosed with COPD and T2DM, 83.9% (26 subjects) were male and 16.1% (5 subjects) were female. In terms of age distribution, the 40–59-year age group had the highest frequency, totaling 18 individuals (58.1%). In terms of occupation, self-employed individuals represented the largest group with 24 subjects (77.4%). For COPD severity, the highest frequency was found in the severe COPD category, with 15 subjects (48.4%). Based on the results of the study investigating the relationship between Type 2 Diabetes Mellitus and the severity of COPD obstruction, a significant relationship was found between T2DM and COPD obstruction severity when analyzed by gender, age, occupation, and the results of spirometry and fasting blood glucose tests.